PEMECAHAN (SPLITTING) MOLEKUL AIR MENJADI GAS H2DAN O2 MELALUI PROSES FOTOVOLTAIK - Fatmi, Dini; Alif, Admin; Suyani, Hamzar (Universitas Andalas, 2012)
One method to overcome the scarcity of alternative sources of energy on earth is through the development of photovoltaic cells. This method used a solar energy to electrical energy transformation. In this research, breaking (splitting) of water molecules into H2 and O2 gas by the photovoltaic process uses electrodes CuO/C with Na2SO4 electrolyte. In this process used 2 photovoltaic cells as electricity producing and U-shaped electrolysis cell for solver (splitting) of water molecule produce H2 and O2 gas. CuO electrode (anode) is made through the burning of copper rod in a furnace at temperature 400 oC with a variety of combustion 1, 3, 4 times each lasting for 1 hs, while the cathode in the form of carbon rods obtained from 2B pencil. The optimum conditions for Na2SO4 electrolyte concentration is 0.8 N and for CuO electrodes with 3x burning. Optimum efficiency photovoltaic process was 2.66%. H2 and O2 gas volume obtained near stoichiometric ratio is 2 : 1.